Analisis Unsur Bawah Sadar Tokoh Novel Merahnya Merah Karya Iwan Simatupang Pemaknaan Dengan Kajian Psikoanalisis = Analysis of Character's Subconscious in Merahnya Merah Novel by Iwan Simatupang Using Psychoanalysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Merahnya Merah is one of contemporary novels written by Iwan Simatupang, which relates to contemplatio, moral conflict, and the characters' problems. The characters have anxiety and kinds of crisis in their life.. The crises are mental, moral, religious and crisis of value and some of the characters hace neurosis. They have behavior deviation and mental destrctuin, because of that as if they were often in imagination wold or subconscious. To know the mental condition of the characters it needs analysis. The analysis used is psychoanalysis by Sigmund Freud. The psychoanalysis used, as the analyses of this novel and the methods developed by Sigmund Freuds are transference and free association. The transference method is used for transferring all the characters' utterances, contemplation, memorization and imagination, shich are noted chronologically. The result of transference can be used to analyze and to find the characters' subconsciousness descriptively. The form of subconsciousness is blur form such as symptoms, dreams, jokes and slip of the tongue in literary works. The free association is used to determine mental mobile and process. Memory, sense and imagination are the controls of free association. The methods can be applied to literary resarch completed with qualitative method that is based on data presented in discourse, not numbers. The tehcniques of analyzing the data are taking note to the result of observation, interviewing or recording, editing, classifying, reducing, and presenting. Based on the analysis of the Merahnya Merah characters' subconscious aspect it was found that the main character often han behaviour deviation that was influenced by his subconscious. The influence proved the role of Ego in giving chance to Id to fulfill the libido. The main character's subconscious that was found, were all about hope that affiliated to Eros as the life instinct and Thanatos as the instinct. The two aspects aimed at loosing the joyless. In fulfilling the joyful the main character sublimated to hace adaption, relief, or chatarsis, but he got failure in his journey facing the death. It showed that any human effort would always fail in reaching and defending the existence if the used Id as the base without the existence of Ego to complete the Superego.